AN ENGLISH ACTION RESEARCH FOR A BETTER LIFE (EBL) - Tarmizi Rasul; imam suseno (Scope : Journal of English Language Teaching, 2020)
English is a foreign language in this country which is needed by all sides especially by teenagers  since English, both competence and performance, will be always needed by workers in all kinds of jobs.  The teenagers in kelurahan Cipedak Jagakarsa South Jakarta have been united in an teenagers organization which is called Karang Taruna. They were enthusiastic to engage in an English Action Research called EBL (English for A Better Life). EBL was an activity as an English action being carried out by implementing  an Oral Questioning Guidance in L1 (OQIGIL) method.  This OQIGIL method aimed at improving the awarness of teaching of a teacher to increase his students’ communication skills. An OQIGIL Method which is developed from time to time was based on a systematic procedure  focused on  a certain quality or a standard, and an accurateness and a certain efficiency as well. After this EBL was undertaken several times, the students’ competence and performance improved better.